(untitled) (Biological Sciences - PJSIR, 2004)
The brain lipid of Baghda chingri (Penaeus monodon) was extracted and characterized with respect to various physical and chemical constants and compared with those of standard oils and fats. Thin layer chromatographic (TLC) and gas liquid chromatographic (GLC) investigation of the lipid showed the presence of myristic, palmitic, stearic, oleic, linoleic, arachidic and some other unidentified fatty acids. The microbial activities of the lipid were investigated. Nitrogen, phosphorus, potassium and calcium contents of the total brain containing the lipid were determined.